Analysis of the Implementation of the Circular Economy System in Waste Banks to Increase Added Value from the Perspectives of Economy, Environment, Social, and Governance (Case Study: Binsik Paser Waste Bank) - Amalia Salwa Najwati; Masiyah Kholmi; Mursidi Mursidi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the implementation of the circular economy system at BINSIK Paser Waste Bank in enhancing added value from the perspectives of economy, environment, social, and governance (ESG). Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation involving waste bank managers, the local community, and the Environmental Agency of Paser Regency. The results indicate that the application of circular economy principles based on the 5Rs (Reduce, Reuse, Recycle, Recovery, and Repair) can increase community income, reduce the volume of waste sent to the final disposal site (TPA), lower carbon emissions, and strengthen community literacy and participation in waste management. Furthermore, good governance of the waste bank is reflected in its clear organizational structure, transaction transparency, and accountable reporting. These findings demonstrate that the implementation of a circular economy in waste banks not only contributes to sustainable development but also simultaneously creates economic and social value through the principle of Creating Shared Value (CSV).